Tingkat Efisiensi Ekonomi Usaha Tani Jagung di Kabupaten Dairi Provinsi Sumatera Utara - Helentina Situmorang; Ratna Winandi; Nunung Nuryartono (Journal of Agribusiness and Community Empowerment (JACE), 2020)
Dairi Regency has the potential to increase its maize production. One of the problems in maize farming is its low productivity because of its low efficiency of input use. The objectives of this research are:(1) analyzing factors influencing maize production, and (2) analyzing the economic efficiency of maize farming at Dairi District. The analysis methods used are the Cobb-Douglas stochastic frontier production function utilizing Maximum Likelihood Estimation (MLE) to analyze technical efficiency, the dual cost function to analyze allocative efficiency. This research used cross-section data. The research findings showed thatfactors like seed and fertilizers (SP-36 and Phonska) were positively and statistically significant on maize production (level of significance at 5 percents), the use of urea and herbicide also havea positive and statistically significant influence on maize production (level of significance at 10 percents). Furthermore, labor use hasa positive, but not statistically significant effect on maize production. The efficiency analysis revealed that the maize farmers had economic inefficiency. The low frequency of extension visits was a substantial contributorto this technical inefficiency. Agricultural extension is deemed essential to significantly increase the technical efficiency.